Polymerizable compound, liquid crystal composition containing polymerizable compound and liquid crystal display device

By introducing a ring structure into the m-terphenyl polymerizable compound, polymerizable compounds with excellent diffusion and antistatic properties were developed, which solved the problems of insufficient antistatic ability and improved diffusion of PSVA liquid crystal displays, and achieved better Show uniformity and electrostatic release effects.

CN119431147AActive Publication Date: 2025-02-14SHIJIAZHUANG CHENGZHI YONGHUA DISPLAY MATERIALS CO LTD

Patent Information

Application Number
CN202510026055.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-07
Publication Date
2025-02-14
Estimated Expiration
2045-01-07

AI Technical Summary

Technical Problem

The existing PSVA liquid crystal displays lack the antistatic ability, and the diffusion and particle size after polymerization need to be further improved, resulting in problems such as electrostatic accumulation, poor display and fragmented highlights.

Method used

By introducing a specific cyclic structure into the m-terphenyl polymerizable compound structure, a new polymerizable compound has been developed, which has small SEM particles, excellent diffusion and antistatic properties upon polymerization.

Benefits of technology

The liquid crystal composition of the polymerizable compound can meet the uniformity requirements of large-size PSVA liquid crystal displays, avoid the occurrence of adverse display phenomena such as broken highlights, and have the ability to quickly release static electricity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119431147A_ABST
    Figure CN119431147A_ABST
Patent Text Reader

Abstract

The invention discloses a polymerizable compound, a liquid crystal composition containing the polymerizable compound and a liquid crystal display device. The polymerizable compound is a compound shown as a formula I, in the formula I, # imgabs 0 # and # imgabs 1 # are respectively and independently represented as # imgabs 2 #, # imgabs 3 # or # imgabs 4 #, and # imgabs 5 # and # imgabs 6 # are not simultaneously represented as # imgabs 7 #; any hydrogen in the # imgabs8 and # imgabs9 can be substituted by alkyl or alkoxy of C1-C5, alkenyl or alkenyloxy of C2-C5, alkyl or alkoxy of C1-C5 substituted by fluorine, alkenyl or alkenyloxy of C2-C5 substituted by fluorine and halogen, and any one or more of-CH2-which is not connected can be independently substituted by-O-,-S-,-CO-,-CH2O-,-OCH2-,-COO-and-OOC-respectively. The polymerizable compound has the advantages of small SEM particles after polymerization and excellent diffusivity and antistatic performance. When being used in a liquid crystal display component, the liquid crystal display component has the advantages of good uniformity, rapid static electricity release and avoidance of bad display phenomena such as broken bright spots. And # imgabs10 # I is adopted.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of liquid crystal display technology, and more specifically to a polymerizable compound, a liquid crystal composition containing the polymerizable compound, and a liquid crystal display device. Background Art

[0002] Thin-film transistor liquid crystal displays (TFT-LCDs) have gone through a long period of basic research. After achieving large-scale production and commercialization, they have become the mainstream product in LCD applications with their advantages such as lightness, environmental protection, and high performance. Whether it is a small mobile phone screen, a large notebook computer (Notebook PC) or monitor (Monitor), or a large-scale LCD TV (LCD-TV), TFT-LCD applications can be seen everywhere.

[0003] Early commercial TFT-LCD products basically adopted the TN display mode, and its biggest problem was the narrow viewing angle. With the increase in product size, especially in the application of TV field, IPS display mode and VA display mode with wide viewing angle characteristics were developed and applied successively, especially the commercialization of large-size PSVA (Polymer stabilized vertically aligned) display, which has the advantages of wide viewing angle, high contrast and no need for rubbing alignment. It adds a small amount (0.3%~1% by weight) of polymerizable compound (RM) to the liquid crystal composition, and after the LC (liquid crystal) medium is filled into the display, it is polymerized or cross-linked in situ (usually by UV light polymerization), and a voltage is optionally applied to the electrodes of the display. The polymerization is carried out at a temperature at which the LC medium shows a liquid crystal phase, usually at room temperature. It has been proven to be particularly suitable to add polymerizable mesogens or polymerizable compounds (also called reactive mesogens or "RM") to the LC mixture. However, the current commercial PSVA displays, especially the RM involved, still have the following problems: Insufficient antistatic ability. In the daily use of PSVA monitors, static electricity is easily generated due to friction with external objects (such as ordinary cloth wiping) or friction between some parts inside the monitor during operation. At the microscopic level, during the movement of liquid crystal molecules, friction static electricity may also be generated between the surrounding orientation layer or other liquid crystal molecules due to relative movement. If the generated static electricity cannot be conducted away in time, it will accumulate inside the monitor and affect the display of the monitor, such as interfering with the signal transmission of the monitor, changing the contrast and brightness of the monitor, etc. In general, the antistatic performance of PSVA monitors plays a very important role in protecting the display panel, improving display quality, enhancing durability and improving user experience: 1) Improve display quality: static electricity interferes with the normal arrangement of liquid crystal molecules, thereby affecting the panel display and causing poor display; 2) Enhance durability: In windy or dry environments, antistatic performance can reduce impurities and dust adsorbed by static electricity, reduce maintenance costs, and enhance durability; 3) Improve user experience: When operating the touch screen, static electricity may interfere with the display, and excellent antistatic performance can improve user experience. At present, in PSVA monitors, polar groups can be introduced into the PI alignment film to improve antistatic ability, but the improvement is still limited.

[0004] The diffusivity and particle size of RM after polymerization need to be further improved. In the prior art, since RM cannot be completely polymerized, it is easy to cause the "image stickiness" effect in the PSVA display. The residual RM monomer is easy to cause uncontrolled polymerization in the backlight or during use, resulting in changes in the pre-tilt angle and thus affecting the uniformity of the display. In addition, due to energy efficiency control, display manufacturers expect the UV treatment time to be as short as possible. Therefore, faster and more completely polymerized RM is expected. However, when the polymerization speed of RM is fast and the diffusivity is poor, it is easy to form implosion, resulting in uncontrolled reaction and easy to make the particle size of the generated polymer layer larger, forming broken bright spots and thus affecting the display effect of the panel. Therefore, RM monomers with fast polymerization speed but excellent diffusivity and small particle size after polymerization are needed. Summary of the invention

[0005] Based on this, the object of the present invention is to provide a polymerizable compound that can simultaneously meet the above requirements or at least meet one of the requirements, a liquid crystal composition containing the polymerizable compound, and a liquid crystal display device. In the polymerizable compound, by introducing a specific ring structure into a specific meta-terphenyl polymerizable compound structure, the polymerizable compound is endowed with the advantages of small SEM particles after polymerization, excellent diffusivity and antistatic properties. As a result, when the liquid crystal composition containing the polymerizable compound is used in a liquid crystal display element or a liquid crystal display (especially a PSVA or SAVA (Self-Alignment for Vertical Alignment) mode display device), it can meet the uniformity requirements of a large-size PSVA type liquid crystal display, and can effectively avoid the occurrence of poor display phenomena such as broken bright spots, has the ability to quickly release static electricity, and has good application value.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions: In one aspect, the present invention provides a polymerizable compound, wherein the polymerizable compound is a compound as shown in Formula I: I; in, R represents H, C1-C5 alkyl or alkoxy, C2-C5 alkenyl or alkenyloxy, fluorine-substituted C1-C5 alkyl or alkoxy, fluorine-substituted C2-C5 alkenyl or alkenyloxy, or halogen; P is a polymerizable group; Sp is a spacer group or a single bond; , Separately expressed: , or ,and , Different ; in , Any hydrogen in the group may be substituted by a C1-C5 alkyl or alkoxy group, a C2-C5 alkenyl or alkenyloxy group, a fluorinated C1-C5 alkyl or alkoxy group, a fluorinated C2-C5 alkenyl or alkenyloxy group, or a halogen group, wherein any one or more unconnected -CH 2 - can be independently replaced by -O-, -S-, -CO-, -CH 2 O-、-OCH 2 -, -COO-, -OOC-substituted.

[0007] Furthermore, the compound represented by formula I is selected from the group consisting of compounds represented by the following formulas I-1 to I-9: I-1, I-2, I-3, I-4, I-5, I-6, I-7, I-8, I-9; in, R represents H, C1-C5 alkyl or alkoxy, C2-C5 alkenyl or alkenyloxy, fluorine-substituted C1-C5 alkyl or alkoxy, fluorine-substituted C2-C5 alkenyl or alkenyloxy, or halogen; P is a polymerizable group; Sp is a spacer group or a single bond; Selected from ,in Any hydrogen in the group may be substituted by a C1-C5 alkyl or alkoxy group, a C2-C5 alkenyl or alkenyloxy group, a fluorinated C1-C5 alkyl or alkoxy group, a fluorinated C2-C5 alkenyl or alkenyloxy group, or a halogen group, wherein any one or more unconnected -CH 2 - can be independently replaced by -O-, -S-, -CO-, -CH 2 O-、-OCH 2 -, -COO-, -OOC-substituted.

[0008] Furthermore, the compounds represented by formulae I-1 to I-9 are selected from the group consisting of compounds represented by the following formulae I-1-1 to I-9-1: I-1-1, I-1-2, I-1-3, I-1-4, I-1-5, I-1-6, I-1-7, I-1-8, I-1-9, I-1-10, I-1-11, I-1-12, I-1-13, I-1-14, I-1-15, I-1-16, I-1-17, I-1-18, I-2-1, I-3-1, I-4-1, I-5-1, I-6-1, I-7-1, I-8-1, I-9-1.

[0009] Furthermore, the polymerizable group is selected from , or , where · represents the connection site.

[0010] In yet another aspect, the present invention provides a liquid crystal composition, comprising one or more polymerizable compounds as described in the first aspect.

[0011] Furthermore, in the liquid crystal composition, the total mass percentage of the polymerizable compound represented by Formula I is 0.01-1%.

[0012] Furthermore, in the liquid crystal composition, the total mass percentage of the polymerizable compound represented by Formula I is 0.1-0.8%.

[0013] Furthermore, the liquid crystal composition further comprises one or more compounds represented by formula II: II; in, R 1 , R 2 Each independently represents a C1-C10 alkyl group or a C2-C10 alkenyl group, wherein one or more non-adjacent -CH 2 - may be replaced by -O-, cyclopropyl, cyclobutyl or cyclopentyl; Z 1 Indicates -CH 2 -CH 2 -, -O-, -CO-O-, -O-CO-, -CH 2 O-、-OCH 2 -, -CH=CH-, -C≡C or single bond; m1 and m2 each independently represent 0, 1 or 2; , Each independently expresses , , , or .

[0014] Furthermore, the liquid crystal composition further comprises one or more compounds represented by formula III: III; in, R 3 , R 4 Each independently represents a C1-C10 alkyl group or a C2-C10 alkenyl group, wherein one or more non-adjacent -CH 2 - may be replaced by -O-, cyclopropyl, cyclobutyl or cyclopentyl; Z 2 Indicates -CH 2 -CH 2 -, -O-, -CO-O-, -O-CO-, -CH 2 O-、-OCH 2 -, -CH=CH-, -C≡C or single bond; m3 means 0, 1 or 2; express , , , or .

[0015] Furthermore, the liquid crystal composition further comprises one or more compounds represented by formula IV: IV; in, R 5 , R 6 Each independently represents a C1-C10 alkyl group or a C2-C10 alkenyl group, wherein one or more non-adjacent -CH 2 - may be replaced by -O-, cyclopropyl, cyclobutyl or cyclopentyl.

[0016] Furthermore, the liquid crystal composition further comprises one or more compounds represented by formula V: V; in, R 7 , R 8Each independently represents H, F, Cl, C1-C10 alkyl or C1-C10 fluoroalkyl, wherein one or more non-adjacent -CH 2 - may be replaced by -O-, cyclopropyl, cyclobutyl or cyclopentyl; X represents -O-, -S-, -CO- or -CH 2 O-; Z 3 Represents -O-, -CO-O-, -O-CO-, -CH 2 O-、-OCH 2 -、-CH=CH-、-CF 2 O- or single bond; express , , , , , , , , , , or ; m4 represents 0 or 1.

[0017] In yet another aspect, the present invention provides a liquid crystal display device, which is prepared from raw materials comprising the liquid crystal composition described in the second aspect above.

[0018] Furthermore, the liquid crystal display device is a PSVA, SAVA, IPS or FFS mode display device.

[0019] The beneficial effects of the present invention are as follows: Compared with the prior art, in the structure of the polymerizable compound provided in the present invention, by introducing a specific ring structure into the meta-terphenyl polymerizable compound, the polymerizable compound has the advantages of small SEM particles after polymerization, excellent diffusivity and antistatic properties, can meet the uniformity requirements of large-size PSVA type liquid crystal displays, and can effectively avoid the occurrence of display defects such as broken bright spots, has the ability to quickly release static electricity, and has good application value. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] The specific implementation modes of the present invention are further described in detail below in conjunction with the accompanying drawings.

[0021] Figure 1 The mass spectrum of polymerizable compound I-1-7 obtained in Synthesis Example 2 is shown. DETAILED DESCRIPTION

[0022] In order to more clearly illustrate the present invention, the present invention is further described below in conjunction with preferred embodiments and accompanying drawings. Similar components in the accompanying drawings are represented by the same reference numerals. It should be understood by those skilled in the art that the content specifically described below is illustrative rather than restrictive, and should not be used to limit the scope of protection of the present invention.

[0023] According to a specific embodiment of the present invention, a polymerizable compound is provided, wherein the polymerizable compound is a compound as shown in Formula I: I; in, R represents H, C1-C5 alkyl or alkoxy, C2-C5 alkenyl or alkenyloxy, fluorine-substituted C1-C5 alkyl or alkoxy, fluorine-substituted C2-C5 alkenyl or alkenyloxy, or halogen; P is a polymerizable group; Sp is a spacer group or a single bond; , Separately expressed: , or ,and , Different ; in , Any hydrogen in the group may be substituted by a C1-C5 alkyl or alkoxy group, a C2-C5 alkenyl or alkenyloxy group, a fluorinated C1-C5 alkyl or alkoxy group, a fluorinated C2-C5 alkenyl or alkenyloxy group, or a halogen group, wherein any one or more unconnected -CH 2 - can be independently replaced by -O-, -S-, -CO-, -CH 2 O-、-OCH 2 -, -COO-, -OOC-substituted.

[0024] In this embodiment, the term "spacer group" is known to those skilled in the art in the prior art and is described in the literature, for example, Pure Appl. Chem. 2001, 73 (5), 888 and C. Tschierske, G. Pelzl, S. Diele, Angew. Chem. 2004, 116, 6340-6368. As used herein, the term "spacer group" refers to a flexible group that connects the mesogen group and the polymerizable group in the polymerizable compound, for example, an alkylene group.

[0025] In some examples, in this embodiment, the "polymerizable group" is preferably an acrylate group ( ), methacrylate group ( ) or fluoroacrylate-based ( ), where · represents the attachment site.

[0026] In the structure of the compound represented by Formula I in this embodiment, the group , By making specific selections, the polymerizable compound has the advantages of small SEM particles after polymerization, excellent diffusivity and antistatic properties, can meet the uniformity requirements of large-size PSVA type liquid crystal displays, and effectively avoid the occurrence of display defects such as broken bright spots, and has the ability to quickly release static electricity.

[0027] In some examples, the compound represented by Formula I is selected from the group consisting of compounds represented by the following Formulas I-1 to I-9: I-1, I-2, I-3, I-4, I-5, I-6, I-7, I-8, I-9; in, R represents H, C1-C5 alkyl or alkoxy, C2-C5 alkenyl or alkenyloxy, fluorine-substituted C1-C5 alkyl or alkoxy, fluorine-substituted C2-C5 alkenyl or alkenyloxy, or halogen; P is a polymerizable group; Sp is a spacer group or a single bond; Selected from ; in Any hydrogen in the group may be replaced by a C1-C5 alkyl or alkoxy group, a C2-C5 alkenyl or alkenyloxy group, a fluorine-substituted C1-C5 alkyl or alkoxy group, a fluorine-substituted C2-C5 alkenyl or alkenyloxy group, or a halogen (e.g., F, Cl), wherein any one or more unconnected -CH 2 - can be independently replaced by -O-, -S-, -CO-, -CH 2 O-、-OCH 2 -, -COO-, -OOC-substituted.

[0028] In some examples, if Any hydrogen in the group may be replaced by a C1-C5 alkyl or alkoxy group, a C2-C5 alkenyl or alkenyloxy group, a fluorine-substituted C1-C5 alkyl or alkoxy group, a fluorine-substituted C2-C5 alkenyl or alkenyloxy group, or a halogen (e.g., F, Cl), wherein any one or more unconnected -CH 2 - can be independently replaced by -O-, -S-, -CO-, -CH 2 O-、-OCH 2 If the alkyl group is substituted by -, -COO- or -OOC-, it is preferably monosubstituted, and more preferably monosubstituted by halogen (such as F) or C1-C5 alkoxy.

[0029] In some examples, the for , , wait.

[0030] In some specific examples, the compounds represented by formulas I-1 to I-9 are selected from the group consisting of compounds represented by the following formulas I-1-1 to I-9-1: I-1-1, I-1-2, I-1-3, I-1-4, I-1-5, I-1-6, I-1-7, I-1-8, I-1-9, I-1-10, I-1-11, I-1-12, I-1-13, I-1-14, I-1-15, I-1-16, I-1-17, I-1-18, I-2-1, I-3-1, I-4-1, I-5-1, I-6-1, I-7-1, I-8-1, I-9-1.

[0031] According to another specific embodiment of the present invention, a liquid crystal composition is provided, wherein the liquid crystal composition comprises one or more polymerizable compounds as described above.

[0032] In some examples, the total mass content of the polymerizable compound represented by Formula I in the liquid crystal composition is 0.01-1%. Adding a small amount of the polymerizable compound represented by Formula I to the liquid crystal composition enables the liquid crystal composition to meet the uniformity requirements of large-size PSVA liquid crystal displays, effectively avoid the occurrence of display defects such as broken bright spots, and has the ability to quickly release static electricity.

[0033] In some specific examples, in the liquid crystal composition, the total mass percentage of the polymerizable compound represented by Formula I includes but is not limited to 0.1-1%, 0.1-0.8%, 0.1-0.5%, 0.2-0.8%, 0.2-0.5%, etc.

[0034] In some examples, the liquid crystal composition further comprises one or more compounds of Formula II, II; in, R 1 , R 2 Each independently represents a C1-C10 alkyl group or a C2-C10 alkenyl group, wherein one or more non-adjacent -CH 2 - may be replaced by -O-, cyclopropyl, cyclobutyl or cyclopentyl; Z 1 Indicates -CH 2 -CH 2 -, -O-, -CO-O-, -O-CO-, -CH 2 O-、-OCH 2 -, -CH=CH-, -C≡C or single bond; m1 and m2 each independently represent 0, 1 or 2; , Each independently expresses , , , or .

[0035] In some examples, the compound represented by Formula II is selected from the group consisting of compounds represented by Formula II-1 to Formula II-10, II-1, II-2, II-3, II-4, II-5, II-6, II-7, II-8, II-9, II-10, in, R 1 , R 2 Each independently represents a C1-C10 alkyl group or a C2-C10 alkenyl group, wherein one or more non-adjacent -CH 2 - may be replaced by -O-, cyclopropyl, cyclobutyl or cyclopentyl.

[0036] In some examples, in the liquid crystal composition, the total mass percentage of the compound represented by Formula II includes but is not limited to 30-60%, 30-55%, 33-55%, etc.

[0037] In some examples, the liquid crystal composition further comprises one or more compounds of Formula III: III; in, R 3 , R 4 Each independently represents a C1-C10 alkyl group or a C2-C10 alkenyl group, wherein one or more non-adjacent -CH 2 - may be replaced by -O-, cyclopropyl, cyclobutyl or cyclopentyl; Z 2 Indicates -CH 2 -CH 2 -, -O-, -CO-O-, -O-CO-, -CH 2 O-、-OCH 2 -, -CH=CH-, -C≡C or single bond; m3 means 0, 1 or 2; express , , , or .

[0038] In some preferred examples, the compound represented by Formula III is selected from the group consisting of compounds represented by Formula III-1 to Formula III-10: III-1, III-2, III-3, III-4, III-5, III-6, III-7, III-8, III-9, III-10, III-11, III-12, III-13, III-14, III-15, III-16, III-17; in, R 3 , R 4 Each independently represents a C1-C10 alkyl group or a C2-C10 alkenyl group, wherein one or more non-adjacent -CH 2 - may be replaced by -O-, cyclopropyl, cyclobutyl or cyclopentyl.

[0039] In some examples, in the liquid crystal composition, the total mass percentage of the compound represented by Formula III includes but is not limited to 40-70%, 43-70%, etc.

[0040] In some examples, the liquid crystal composition further comprises one or more compounds of Formula IV: IV; in, R 5 , R 6 Each independently represents a C1-C10 alkyl group or a C2-C10 alkenyl group, wherein one or more non-adjacent -CH 2 - may be replaced by -O-, cyclopropyl, cyclobutyl or cyclopentyl.

[0041] In some preferred examples, the compound represented by the aforementioned formula IV is selected from the group consisting of compounds represented by formula IV-1 to formula IV-6, IV-1, IV-2, IV-3, IV-4, IV-5, IV-6.

[0042] In some examples, in the liquid crystal composition, the total mass percentage of the compound represented by Formula IV includes but is not limited to 1-5%, 2-5%, 2-4%, etc.

[0043] In some preferred examples, the liquid crystal composition further comprises one or more compounds represented by formula V: V; in, R 7 , R 8 Each independently represents H, F, Cl, C1-C10 alkyl or C1-C10 fluoroalkyl, wherein one or more non-adjacent -CH 2 - may be replaced by -O-, cyclopropyl, cyclobutyl or cyclopentyl; X represents -O-, -S-, -CO- or -CH 2 O-; Z 3 Represents -O-, -CO-O-, -O-CO-, -CH 2 O-、-OCH 2 -、-CH=CH-、-CF 2 O- or single bond; express , , , , , , , , , , or ; m4 represents 0 or 1.

[0044] In some preferred examples, the compound represented by formula V is selected from the group consisting of compounds represented by formula V-1 to formula V-6, V-1, V-2, V-3, V-4, V-5, V-6, V-7, V-8, V-9, V-10, V-11; Among them, R 7 , R 8 Each independently represents H, F, Cl, C1-C10 alkyl or C1-C10 fluoroalkyl, wherein one or more non-adjacent -CH 2 - may be replaced by -O-, cyclopropyl, cyclobutyl or cyclopentyl.

[0045] In some examples, in the liquid crystal composition, the total mass percentage of the compound represented by Formula V includes but is not limited to 1-5%, 2-5%, 2-4%, etc.

[0046] The polymerizable compound (containing a cyclic meta-terphenyl polymerizable compound) provided in the embodiment of the present invention and the liquid crystal composition formed by combining the polymerizable compound with a specific liquid crystal component are suitable for liquid crystal display elements or liquid crystal displays, especially for PSVA used in liquid crystal displays or TVs, and PSVA-IPS liquid crystals in IPS mode. Compared with the prior art, the polymerizable compound shown in Formula I has the advantages of small SEM particles after polymerization, excellent diffusivity and antistatic properties by introducing a cyclic structure into the meta-terphenyl polymerizable compound, can meet the uniformity requirements of large-size PSVA-type liquid crystal displays, and effectively avoid the occurrence of display defects such as broken bright spots, and has the ability to quickly release static electricity, and has good application value.

[0047] Dopants with various functions may also be added to the liquid crystal composition provided in this embodiment. In the liquid crystal composition, the mass percentage of the dopants is preferably between 0.01-1%. These dopants are mainly antioxidants, ultraviolet absorbers, and chiral agents.

[0048] Exemplary antioxidants, UV absorbers are preferably selected from the following compounds: , , , , , , ; Here, S represents an integer of 1-10.

[0049] According to another specific embodiment of the present invention, a liquid crystal display device is provided. The liquid crystal display device is prepared from raw materials including the liquid crystal composition as described above.

[0050] Furthermore, the liquid crystal display device is a PSVA (Polymer stabilized vertically aligned), SAVA (Self-Alignment for Vertical Alignment), IPS (In-Plane Switching) or FFS (Fringe Field Switching) mode display device.

[0051] The technical solution of the present invention is described below in conjunction with some specific embodiments: In the present invention, the preparation methods are conventional methods unless otherwise specified, and the raw materials used are all available from public commercial channels unless otherwise specified. The progress of the reaction is generally monitored by TLC, and the post-treatment after the reaction is generally washing with water, extraction, drying after combining the organic phases, evaporating the solvent under reduced pressure, and recrystallization, column chromatography. Those skilled in the art can implement the present invention according to the following description.

[0052] The percentages in this manual refer to mass percentages, and the temperature is in degrees Celsius (℃). The specific meanings of other symbols and test conditions are as follows: Cp represents the clearing point of liquid crystal (℃), measured by DSC quantitative method; SN represents the melting point of the liquid crystal from the crystalline state to the nematic phase (°C); Δn represents optical anisotropy, Δn=ne-no, where no is the refractive index of ordinary light, ne is the refractive index of extraordinary light, and the test conditions are 25±2℃, 589nm, and Abbe refractometer test; Δε represents dielectric anisotropy, Δε=ε∥-ε⊥, where ε∥ is the dielectric constant parallel to the molecular axis, and ε⊥ is the dielectric constant perpendicular to the molecular axis. The test conditions are 25±0.5℃, 20 micron vertical box, INSTEC:ALCT-IR1 test; K11 is the splay elastic constant, K33 is the bending elastic constant, and the test conditions are: 25°C, INSTEC:ALCT-IR1, 20 μm vertical box; γ1 represents rotational viscosity (mPa·s), the test conditions are 25±0.5℃, 20 μm vertical box, INSTEC: ALCT-IR1 test; In this experiment, UV-LED lamps were used to test the test box because they have a narrower emission peak and show less energy consumption, longer life and more efficient light energy transfer to the LC medium, which enables the UV intensity and / or UV irradiation time to be reduced, which can shorten the process time and save energy and production costs. 365nm UV-LED lamps were used in this experiment.

[0053] The test boxes used in the above SEM particle size (nm) and antistatic ability tests are all PSVA type (including Nissan PI) electrode test boxes with a box thickness of 3.5μm. A certain voltage is applied to the test box, and the above 365nm UV-LED lamp is used to perform UV1 irradiation to polymerize the polymerizable compound to form a preliminary pre-tilt angle; then the voltage is removed and the liquid crystal composition that has formed a preliminary pre-tilt angle is continuously irradiated with the above 365nm UV-LED lamp for UV2 treatment to eliminate the residual polymerizable compound in the preliminary pre-tilt state and obtain the final stable pre-tilt angle.

[0054] SEM particle size (nm). The SEM particle size level indicates the density of the film formed by RM. The smaller the particles, the better the density of the film. After the liquid crystal composition containing the polymerizable compound is polymerized under the same UV light conditions (UV1+UV2), the liquid crystal molecules are washed away and the polymerized polymer layer is scanned using a scanning electron microscope (SEM).

[0055] Antistatic ability test: Use conductive tape to remove static electricity from the PSVA box that has undergone the same conditions and a complete UV process (UV1+UV2) and leave it for a while. Tear off the conductive tape before testing and record the time (s) for the final Tr (transmission rate) to return to the initial state. Use an electrostatic gun to apply a 10kV voltage to the cell surface. While powering on, use a display color analyzer (CA410) to monitor the change in the brightness (Lv) of the test box. Read the power-on time and the Tr recovery time. The difference between the two is the static discharge time. The shorter the time, the better the static discharge effect. Measurement of RM diffusivity (distribution behavior of additives): In an environment without UV light, fill the test box (8cm×4cm) with the test mixture. After the mixture is filled, slice the lower part of the test box (close to the filling opening, 4cm×4cm) and the upper part of the test box (opposite to the filling opening, 4cm×4cm). Under the same temperature and wavelength, the gradient method is used to detect the RM content in the lower and upper parts respectively. Instrument: Agilent1200. The quality of diffusivity is determined by the concentration difference. The concentration difference between the lower and upper parts Δ=lower RM content-upper RM content. The smaller Δ is, the better the diffusivity is. In this experiment, a test box with NissanPI upper and lower substrates is used, and the box thickness is 4.0 um.

[0056] The preparation method of the liquid crystal composition is as follows: each liquid crystal monomer is weighed according to a certain ratio and put into a stainless steel beaker, and the stainless steel beaker containing each liquid crystal monomer is placed on a magnetic stirring instrument to heat and melt. After most of the liquid crystal monomers in the stainless steel beaker are melted, a magnetic rotor is added to the stainless steel beaker, and the mixture is stirred evenly. After cooling to room temperature, the liquid crystal composition is obtained.

[0057] The liquid crystal monomer structure of the embodiment of the present invention is represented by a code, and the code representation method of the liquid crystal ring structure, end group, and connecting group is shown in Table 1 and Table 2 below.

[0058] Table 1 Corresponding codes of ring structures

[0059] Table 2 Corresponding codes of terminal groups and linking groups

[0060] Example: , whose code is COY-3-O2; , whose code is PP-5-3; , its code is CY-3-O2; , its code is CC-Cp-V1; , whose code is PGP-Cpr1-2.

[0061] Compound Examples The polymerizable compound of the present invention having a structural formula as shown in Formula I can be synthesized by the following synthetic route: The compounds of the formula I and its subformulae and the intermediates can be prepared analogously to the methods known to the person skilled in the art and described in standard texts of organic chemistry (eg in Houben-Weyl, Methoden der organischen Chemie [Methods of Organic Chemistry], Thieme-Verlag, Stuttgart).

[0062] For example, acrylates or methacrylates can be prepared by esterification of the corresponding alcohol with an acid derivative, such as (meth)acryloyl chloride or (meth)acrylic anhydride, in the presence of a base such as pyridine or triethylamine and 4-(N,N-dimethylamino)pyridine (DMAP). Alternatively, the esters can be prepared by esterification of the alcohol with (meth)acrylic acid in the presence of a dehydrating agent, for example according to Steglich with dicyclohexylcarbodiimide (DCC), N-(3-dimethylaminopropyl)-N'-ethylcarbodiimide (EDC) or N-(3-dimethylaminopropyl)-N'-ethylcarbodiimide hydrochloride and DMAP.

[0063] The present invention is described below using the following specific embodiments.

[0064] Synthesis example 1 Preparation of polymerizable compound I-1-1: The preparation route is as follows:

[0065]

[0066] Intermediate 3: In a nitrogen atmosphere, 0.1 mol of compound 1, 0.095 mol of compound 2, 0.11 mol of potassium carbonate, 0.0005 mol of Pd-132, 0.3 L of toluene and 0.1 L of water were added to a 1000 mL three-necked flask. After the addition was completed, the temperature was raised to about 90 °C and refluxed at this temperature for 1 h; the temperature was lowered to room temperature, the liquids were separated, and the mixture was extracted three times with 0.3 L of toluene, with 0.1 L of toluene used each time. The organic phase was washed with water, dried and rotary evaporated to obtain 35 g of colorless oily intermediate 3 with a yield of 90%.

[0067] Intermediate 5: In a nitrogen atmosphere, 0.06 mol of intermediate 3, 0.066 mol of compound 4, 0.072 mol of potassium carbonate, 0.0005 mol of Pd-132, 0.3 L of toluene and 0.1 L of water were added to a 1000 mL three-necked flask. After the addition was completed, the temperature was raised to about 90 °C and refluxed at this temperature for 1 h; the temperature was lowered to room temperature, the liquids were separated, and the mixture was extracted three times with 0.3 L of toluene, with 0.1 L of toluene used each time. The organic phase was washed with water, dried and rotary evaporated to obtain 28 g of colorless oily intermediate 5 with a yield of 93%.

[0068] Intermediate 6: 0.06 mol of intermediate 5, 300 mL of ethyl acetate and 1.4 g of palladium-carbon hydrogenation catalyst (palladium content of 5 wt%) were added to a 1000 mL three-necked flask. After nitrogen replacement, hydrogen was introduced and the hydrogenation reaction was carried out at room temperature for 24 h. Filter and rotary evaporate to obtain 20 g of colorless oily intermediate 6 with a yield of 98%.

[0069] Product I-1-1: In a 1L three-necked flask, add 0.1mol of intermediate 6, 0.29mol of methacrylic acid, 0.019mol of DMAP and 0.3L of tetrahydrofuran, cool down to 0°C under nitrogen protection, control the temperature at 0-5°C, add 0.29mol of DCC, and after the addition, naturally warm up to room temperature and react at room temperature for 12 hours; remove the solid in the reaction by suction filtration, and evaporate the mother liquor to obtain a yellow oil, which can be further purified by recrystallization from ethanol and toluene to obtain 20g of white solid product I-1-1 with a yield of 88%.

[0070] Using a similar method, the synthesis of the following examples was completed through simple replacement of raw materials: I-2-1, I-3-1.

[0071] I-4-1, I-5-1, I-6-1.

[0072] Synthesis example 2 Preparation of polymerizable compound I-1-7: The preparation route is as follows:

[0073]

[0074]

[0075] Specific operation process of preparation: Intermediate 8: In a nitrogen atmosphere, 0.1 mol of compound 7, 0.095 mol of compound 2, 0.11 mol of potassium carbonate, 0.0005 mol of Pd-132, 0.3 L of toluene and 0.1 L of water were added to a 1000 mL three-necked flask. After the addition, the temperature was raised to about 90 °C and refluxed at this temperature for 1 h. The temperature was lowered to room temperature, the liquids were separated, and the mixture was extracted three times with 0.3 L of toluene, with 0.1 L of toluene used each time. The organic phase was washed with water, dried and rotary evaporated to obtain 35 g of colorless oily intermediate 8 with a yield of 85%.

[0076] Intermediate 9: In a nitrogen atmosphere, 0.06 mol of intermediate 8, 0.066 mol of compound 4, 0.072 mol of potassium carbonate, 0.0005 mol of Pd-132, 0.3 L of toluene and 0.1 L of water were added to a 1000 mL three-necked flask. After the addition, the temperature was raised to about 90 °C and refluxed at this temperature for 1 h; the temperature was lowered to room temperature, the liquids were separated, and the mixture was extracted three times with 0.3 L of toluene, with 0.1 L of toluene used each time. The organic phase was washed with water, dried and rotary evaporated to obtain 30 g of colorless oily intermediate 9 with a yield of 95%.

[0077] Intermediate 10: 0.06 mol of intermediate 9, 300 mL of ethyl acetate and 1.5 g of palladium-carbon hydrogenation catalyst (palladium content 5 wt%) were added to a 1000 mL three-necked flask. After nitrogen replacement, hydrogen was introduced and the reaction was hydrogenated at room temperature for 24 h. Filtered with suction and rotary evaporated to obtain 19.7 g of colorless oily intermediate 10 with a yield of 96%.

[0078] Intermediate 11: 0.06 mol of intermediate 10, 0.18 mol of imidazole and 300 mL of tetrahydrofuran were added to a 1000 mL three-necked flask, and 0.16 mol of tert-butyldimethylsilyl chloride was added in batches. The mixture was reacted at room temperature for 1 h. 200 mL of water was added to the reaction mixture, and the mixture was separated. The mixture was extracted with 0.3 L of ethyl acetate for 3 times, with 0.1 L of ethyl acetate used each time. The organic phase was washed with water, dried, and rotary evaporated to obtain 33 g of colorless oily intermediate 11 with a yield of 96%.

[0079] Intermediate 12: 0.09 mol of bromomethyl triphenylphosphine and 300 mL of tetrahydrofuran were added to a 1000 mL three-necked flask, and 0.09 mol of potassium tert-butoxide was added in batches under a nitrogen atmosphere at 0°C, and the reaction was kept warm for 1 h; 0.06 mol of THF solution of intermediate 11 was added dropwise, and the reaction was carried out at room temperature for 1 h; 100 mL of water was added and the mixture was separated, and the mixture was extracted twice with 0.2 L of ethyl acetate, with 0.1 L of ethyl acetate used each time. The organic phase was washed with water, dried, and rotary evaporated, and then 200 mL of petroleum ether was added for pulping, and the mixture was passed through a column. 200 mL of petroleum ether was used to flush the column, and 33 g of colorless oily intermediate 12 was obtained by rotary evaporation, with a yield of 96%.

[0080] Intermediate 13: 0.06 mol of intermediate 12 and 300 mL of tetrahydrofuran were added to a 1000 mL three-necked flask, and 0.15 mol of tetrabutylammonium fluoride (tetrahydrate) in tetrahydrofuran solution was added dropwise at 0°C, and the mixture was reacted at room temperature for 1 h. 200 mL of water was added to the reaction mixture, and the mixture was separated and extracted with 0.3 L of ethyl acetate for 3 times, with 0.1 L of ethyl acetate used each time. The organic phase was washed with water, dried, and rotary evaporated to obtain 19 g of colorless oily intermediate 13, with a yield of 93%.

[0081] Product I-1-7: In a 1000mL three-necked flask, add 0.06mol of intermediate 13, 0.24mol of methacrylic acid, 0.12mol of DMAP and 200mL of tetrahydrofuran, cool to 0°C under nitrogen protection, control the temperature at 0-5°C, add 0.24mol of DCC, and after the addition, naturally warm to room temperature and react at room temperature for 12 hours; remove the solid in the reaction by suction filtration, and evaporate the mother liquor to obtain a colorless oil, which can be further purified by recrystallization from ethanol and toluene to obtain 24g of white solid product I-1-7 with a yield of 90%.

[0082] The mass spectrum of the compound of formula I-1-7 is as follows Figure 1 shown.

[0083] Using a similar method, the synthesis of the following examples was completed through simple replacement of raw materials: I-1-4, I-1-5, I-1-6, I-1-8, I-1-9, I-1-10, I-1-11, I-1-12, I-1-13, I-1-14, I-1-15, I-1-16, I-1-17, I-1-18.

[0084] The following is further explained by mixing different mother liquid crystal compositions with polymerizable compounds (examples) represented by the general formula I of the present invention in Table 3 and polymerizable compounds widely used in the prior art (comparative examples, D-1, D-2 and D-3), and testing various properties under different conditions.

[0085] Table 3 Structure and code of polymerizable compounds

[0086] The liquid crystal composition SLC-1 matrix and the corresponding properties are shown in Table 4 below.

[0087] Table 4 Liquid crystal composition SLC-1 matrix and corresponding properties

[0088] Each polymerizable compound was added to 100 wt % of the liquid crystal composition SLC-matrix 1 at a mass ratio of 0.3 wt %, and then poured into a liquid crystal box. The performance parameters are shown in Table 5 below.

[0089] Table 5 Performance related data of each liquid crystal composition

[0090] From the data in Table 5, it can be seen that compared with the polymerizable compounds D-1 and D-2 commonly used in the prior art, the diffusivity (Δ: ppm) of the polymerizable compounds containing general formula I in this experiment is all below 30 ppm, while the comparative examples are all above 65 ppm, and the embodiments involving the polymerizable compounds shown in general formula I have better diffusivity. Secondly, the SEM particle size generated by the polymerizable compounds shown in general formula I after the UV process is all below 120 nm, which is at least 60 nm smaller than the comparative example. The SEM particle size of the embodiment is smaller, which can effectively avoid the occurrence of display defects such as broken bright spots. It can be found from the antistatic release speed of the embodiment and the comparative example that the antistatic release speed of the embodiment is much faster than that of the comparative example, and the antistatic ability is stronger.

[0091] Table 6 Matrix of liquid crystal composition SLC-2 and its corresponding properties

[0092] The polymerizable compounds I-1-4, I-1-11, D-1 and D-2 were respectively added to 100wt% of the liquid crystal composition SLC-2 matrix (whose formula and properties are shown in Table 6 above) at a mass ratio of 0.3wt%, and then poured into a liquid crystal box. The performance parameters are shown in Table 7 below.

[0093] Table 7 Performance related data of I-1-4, I-1-11, D-1 and D-2

[0094] It can be seen from the data in Table 7 that the polymerizable compound containing the general formula I of the present invention has better diffusivity, smaller SEM particle size, faster antistatic release speed and stronger antistatic ability.

[0095] Table 8 Matrix of liquid crystal composition SLC-3 and its corresponding properties

[0096] The polymerizable compounds I-1-13, I-1-14, I-3-1 and D-3 were respectively added to 100wt% of the liquid crystal composition SLC-3 matrix (whose formula and properties are shown in Table 8 above) at a mass ratio of 0.3wt%, and then poured into a liquid crystal box. The performance parameters are shown in Table 9 below.

[0097] Table 9 Performance related data of I-1-13, I-1-14, I-3-1 and D-3

[0098] It can be seen from the data in Table 9 that compared with the polymerizable compound D-3 commonly used in the prior art, the polymerizable compound containing general formula I in this experiment has better diffusion, the SEM particle size generated after the UV process is smaller, the antistatic release rate is much faster than the comparative example, and the antistatic ability is stronger. From the perspective of chemical structure, the m-terphenyl RM of this specific structure has a smaller spatial structure than the p-terphenyl RM. When the m-terphenyl RM introduces a large steric hindrance group (such as a cyclocyclic group) at the side position, it is not easy to undergo intramolecular cross-linking polymerization and implode to form large particles, and is more inclined to undergo intermolecular cross-linking polymerization to form small particles. Therefore, the polymerizable compound of the present invention can have the advantages of small SEM particles on the basis of excellent diffusion performance and antistatic performance, and effectively avoid the occurrence of poor display problems such as broken bright spots.

[0099] In summary, the liquid crystal composition containing the polymerizable compound in the present invention has the advantages of small SEM particles after polymerization, excellent diffusivity and antistatic properties, can meet the uniformity requirements of large-size PSVA type liquid crystal displays, and effectively avoid the occurrence of display defects such as broken bright spots, and has the ability to quickly release static electricity, and has good application value.

[0100] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not limitations on the implementation methods of the present invention. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is impossible to list all the implementation methods here. All obvious changes or modifications derived from the technical solution of the present invention are still within the protection scope of the present invention.

Claims

1. A polymerizable compound, characterized in that The polymerizable compound is a compound as shown in Formula I: I; in, R represents H, C1-C5 alkyl or alkoxy, C2-C5 alkenyl or alkenyloxy, fluorine-substituted C1-C5 alkyl or alkoxy, fluorine-substituted C2-C5 alkenyl or alkenyloxy, or halogen; P is a polymerizable group; Sp is a spacer group or a single bond; , Separately expressed: , or ,and , Different ; in , Any hydrogen can be replaced by C1-C5 alkyl or alkoxy, C2-C5 alkenyl or alkenyloxy, fluorine-substituted C1-C5 alkyl or alkoxy, fluorine-substituted C2-C5 alkenyl or alkenyloxy, or halogen, and any one or more unconnected -CH2- can be independently replaced by -O-, -S-, -CO-, -CH2O-, -OCH2-, -COO-, or -OOC-.

2. The polymerizable compound according to claim 1, characterized in that The compound represented by formula I is selected from the group consisting of compounds represented by the following formulas I-1 to I-9: I-1、 I-2、 I-3、 I-4、 I-5、 I-6、 I-7、 I-8、 I-9; in, Selected from ,in Any hydrogen can be replaced by C1-C5 alkyl or alkoxy, C2-C5 alkenyl or alkenyloxy, fluorine-substituted C1-C5 alkyl or alkoxy, fluorine-substituted C2-C5 alkenyl or alkenyloxy, or halogen, and any one or more unconnected -CH2- can be independently replaced by -O-, -S-, -CO-, -CH2O-, -OCH2-, -COO-, or -OOC-.

3. The polymerizable compound according to claim 2, characterized in that The compounds represented by formulae I-1 to I-9 are selected from the group consisting of compounds represented by the following formulae I-1-1 to I-9-1: I-1-1、 I-1-2、 I-1-3、 I-1-4、 I-1-5、 I-1-6、 I-1-7、 I-1-8、 I-1-9、 I-1-10、 I-1-11、 I-1-12、 I-1-13、 I-1-14、 I-1-15、 I-1-16、 I-1-17、 I-1-18、 I-2-1、 I-3-1、 I-4-1、 I-5-1、 I-6-1、 I-7-1、 I-8-1、 I-9-1。 4. The polymerizable compound according to any one of claims 1 to 3, characterized in that The polymerizable group is selected from , or , where · represents the connection site.

5. A liquid crystal composition, characterized in that: The liquid crystal composition comprises one or more polymerizable compounds according to any one of claims 1 to 4.

6. The liquid crystal composition according to claim 5, characterized in that: In the liquid crystal composition, the total mass percentage of the polymerizable compound represented by Formula I is 0.01-1%.

7. The liquid crystal composition according to claim 5, characterized in that: The liquid crystal composition further comprises one or more compounds represented by formula II: II; in, R1 and R2 each independently represent a C1-C10 alkyl group or a C2-C10 alkenyl group, wherein one or more non-adjacent -CH2- groups may be replaced by -O-, cyclopropyl, cyclobutyl or cyclopentyl; Z1 represents -CH2-CH2-, -O-, -CO-O-, -O-CO-, -CH2O-, -OCH2-, -CH=CH-, -C≡C or a single bond; m1 and m2 each independently represent 0, 1 or 2; , Each independently expresses , , , or ; and / or The liquid crystal composition further comprises one or more compounds represented by formula III: III; in, R3 and R4 each independently represent a C1-C10 alkyl group or a C2-C10 alkenyl group, wherein one or more non-adjacent -CH2- groups may be replaced by -O-, cyclopropyl, cyclobutyl or cyclopentyl; Z2 represents -CH2-CH2-, -O-, -CO-O-, -O-CO-, -CH2O-, -OCH2-, -CH=CH-, -C≡C or a single bond; m3 means 0, 1 or 2; express , , , or ; and / or The liquid crystal composition further comprises one or more compounds represented by formula IV: IV; in, R5 and R6 each independently represent a C1-C10 alkyl group or a C2-C10 alkenyl group, wherein one or more non-adjacent -CH2- groups may be replaced by -O-, cyclopropyl, cyclobutyl or cyclopentyl.

8. The liquid crystal composition according to claim 5, characterized in that: The liquid crystal composition further comprises one or more compounds represented by formula V: V; in, R7 and R8 each independently represent H, F, Cl, C1-C10 alkyl or C1-C10 fluoroalkyl, wherein one or more non-adjacent -CH2- may be replaced by -O-, cyclopropyl, cyclobutyl or cyclopentyl; X represents -O-, -S-, -CO- or -CH2O-; Z3 represents -O-, -CO-O-, -O-CO-, -CH2O-, -OCH2-, -CH=CH-, -CF2O- or a single bond; express , , , , , , , , , , or ; m4 represents 0 or 1.

9. A liquid crystal display device, characterized in that: The liquid crystal composition is prepared from raw materials comprising the liquid crystal composition as described in any one of claims 5 to 8.

10. The liquid crystal display device according to claim 9, characterized in that: The liquid crystal display device is a PSVA, SAVA, IPS or FFS mode display device.

Citation Information

Patent Citations

  • Polymerisable compounds and use thereof in liquid-crystal displays

    CN105315157A

  • Liquid crystal composition and liquid crystal display element

    CN108084029A

  • Compound, liquid crystal composition, liquid crystal display element and liquid crystal display device

    CN111253354A

  • Compound, liquid crystal composition and application thereof

    CN113277946A

  • KR20250001026A

Cited By

  • Liquid crystal composition and liquid crystal display element or liquid crystal display comprising same

    CN120904908A

  • Liquid crystal composition and liquid crystal display element or liquid crystal display comprising the same

    CN120904908B